Descriptive analysis of childbirth healthcare costs in an area with high levels of immigration in Spain - Sala Maria; Català Laura; Comas Mercè; Payà Antoni; Sala Assumpció; Del Amo Elisabeth; Castells Xavier; Cots Francesc (BMC, 2011)
Abstract Background The aim of this study was to estimate the cost of childbirth in a teaching hospital in Barcelona, Spain, including the costs of prenatal care, delivery and postnatal care (3 months). Costs were assessed by taking into account maternal origin and delivery type. Methods We performed a cross-sectional study of all deliveries in a teaching hospital to mothers living in its catchment area between October 2006 and September 2007. A process cost analysis based on a full cost accounting system was performed. The main information sources were the primary care program for sexual and reproductive health, and hospital care and costs records. Partial and total costs were compared according to maternal origin and delivery type. A regression model was fit to explain the total cost of the childbirth process as a function of maternal age and origin, prenatal care, delivery type, maternal and neonatal severity, and multiple delivery. Results The average cost of childbirth was 4,328€, with an average of 18.28 contacts between the mother or the newborn and the healthcare facilities. The delivery itself accounted for more than 75% of the overall cost: maternal admission accounted for 57% and neonatal admission for 20%. Prenatal care represented 18% of the overall cost and 75% of overall acts. The average overall cost was 5,815€ for cesarean sections, 4,064€ for vaginal instrumented deliveries and 3,682€ for vaginal non-instrumented deliveries (p < 0.001). The regression model explained 45.5% of the cost variability. The incremental cost of a delivery through cesarean section was 955€ (an increase of 31.9%) compared with an increase of 193€ (6.4%) for an instrumented vaginal delivery. The incremental cost of admitting the newborn to hospital ranged from 420€ (14.0%) to 1,951€ (65.2%) depending on the newborn's severity. Age, origin and prenatal care were not statistically significant or economically relevant. Conclusions Neither immigration nor prenatal care were associated with a substantial difference in costs. The most important predictors of cost were delivery type and neonatal severity. Given the impact of cesarean sections on the overall cost of childbirth, attempts should be made to take into account its higher cost in the decision of performing a cesarean section.